Editorial: biologic therapies for primary sclerosing cholangitis—more disappointment than promise? Authors' reply. Issue 5 (9th August 2018) - Tse, C. S.; Loftus, E. V.; Raffals, L. E.; Gossard, A. A.; Lightner, A. L.
Abstract : Linked Content This article is linked to Tse et al and Ma and Kotze paper. To view these articles visithttps://doi.org/10.1111/apt.14829 andhttps://doi.org/10.1111/apt.14858 .